Vital pulpotomy in the primary dentition: attitudes and practices of community dental staff in Wales - EMMA JANE HINGSTON, SHARLENE PARMAR & MARGARET LINDSAY HUNTER (IAPD and Blackwell, 2007)
The International Agency for Research on Cancer (IARC) has classified formaldehyde as carcinogenic to humans, leaving the dental profession to look for viable substitutes to formocresol in the vital pulpotomy technique. This study was designed to examine the attitudes and practices of Community Dental Service (CDS) staff in Wales in relation to vital pulpotomy for primary molars 18 months following the IARC’s press release.